Model Pemberdayaan Masyarakat Dalam Pencegahan Anemia Pada Remaja Putri Melalui Pemanfaatan Tanaman Obat Keluarga (TOGA) - Nawang Sari, Dewi; Hasanah, Neneng; Herlina, Lina; Akaputri, Della Erriani; M Solehah, Siti; Rahmalia, Desi (LPPM Universitas Respati Indonesia, 2025)
Anemia among adolescent girls remains a significant public health issue in Indonesia. The utilization of Family Medicinal Plants (TOGA) has potential as a preventive strategy by improving iron intake. Objective: This study aims to evaluate the effectiveness of community empowerment based on TOGA in preventing anemia among adolescent girls.A mixed-method approach was applied with total sampling of 30 adolescent girls aged 12–18 years. The intervention included health education, TOGA cultivation training, and preparation of TOGA-based foods and beverages. Quantitative data were analyzed using paired t-tests for knowledge scores and hemoglobin levels, and Chi-square tests for the proportion of mild anemia, with a significance level of α = 0.05. Qualitative data were analyzed through transcription, coding, and triangulation. Knowledge scores increased from 55% to 75% (p = 0.001), awareness of hemoglobin testing increased from 50% to 83% (p = 0.003), and willingness to consume TOGA-based products increased from 40% to 70% (p = 0.002). Mean hemoglobin levels increased from 11.3 g/dL to 12.0 g/dL (p = 0.021), with a decrease in mild anemia prevalence from 30% to 20% (p = 0.015). Qualitative analysis highlighted the importance of family support, health cadres, and a supportive environment in enhancing intervention success. The community empowerment model based on TOGA is effective in improving knowledge, healthy behaviors, and hemoglobin status among adolescent girls.